209k views
5 votes
3(a + 4) – 5(a – 2) = 22

User Matanso
by
5.0k points

2 Answers

5 votes

Answer:

0

Explanation:

3(a + 4) - 5(a - 2) = 22

3a + 12 - 5a + 10 = 22

-2a + 22 = 22

-2a = 0

a = 0

I hope this helps you :)

User Rosiane
by
5.6k points
2 votes


\text {Hey! Let's Solve this Problem!}


\text {\underline {The First Step is to Simplify}}


\text {3*a=3a \rightarrow {3*4=12}}
\text {3*a=3a}\\\text {3*4=12}


\text {-5*a=-5a}\\\text {-5*-2=10}


\text {Your New Problem Is: 3a+12+-5a+10=22}


\text {\underline {The Next Step is to Combine Like Terms}}


\text {3a+-5a=-2a}\\\text {12+10=22}


\text {Your New Problem Is: -2a+22=22}


\text {\underline {The Next Step is to Subtract 22}}


\text {-2a+22-22=22-22}


\text {Your New Problem Is: -2a=0}


\text {\underline {The Final Step is to Divide 2}}


\text {-2a/2=0/2}


\text {Your Answer Would Be:}


\huge\boxed {a=0}


\text {Best of Luck!}

User Djamel
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.